Pemanfaatan Sistem Pengambilan Keputusan dalam Penentuan Bantuan Modal Usaha di Desa Latta, Kecamatan Baguala, Kota Ambon - Tetelepta, Edward Gland; Helmi, Dewilna (Universitas Pattimura, 2023)
Decision Support System (DSS) is an interactive information system that provides information, modeling, and data manipulation to assist decision-making in semi-structured and unstructured situations. DSS is usually developed using a flexible and interactive Computer Based Information System (CBIS). Implemented as a solution in the context of business capital assistance in Latta Village, DSS aims to understand and produce an up-to-date information system for Latta Village residents' database, as well as support the decision-making process related to the allocation of business capital assistance. Another main objective is to ensure the accuracy and completeness of the data used in decision-making to prevent targeting errors and ensure data selection in accordance with predetermined criteria. The community service program involves lectures by competent academics and practitioners in their fields. Through the utilization of the decision-making system in determining business capital assistance in Latta Village, Baguala District, Ambon City, participants and village officials gain an in-depth understanding of the citizen database information system. The application of the computerized system has proven significant benefits for policy makers, becoming an effective tool in supporting accurate decision-making for the type of business capital assistance that suits the needs and potential of the local community. Through the mentoring process, village officials demonstrated good skills in managing databases and determining the latest business capital assistance. This success creates a better information environment and empowers village officials to improve the welfare of the community in Latta Village.